Analisis Laporan Keuangan Perbandingan Kinerja Keuangan Perusahaan Farmasi Di Indonesia (Studi Pada PT. Kalbe Farma, PT. Kimia Farma, Dan PT. Sidomuncul Periode 2019-2023) - Theresia Uli Sianturi; Nouva Ayu R; Dania Salsabela (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to analyze the financial performance of three pharmaceutical companies in Indonesia, namely PT Kalbe Farma Tbk, PT Kimia Farma Tbk, and PT Sido Muncul Tbk, in the period 2019–2023. The analysis was carried out using financial ratios including liquidity, activity, solvency, and profitability ratios to evaluate the financial stability and efficiency of each company. The data used are secondary data from financial reports.The results of the study show that PT Kalbe Farma Tbk and PT Sido Muncul Tbk have stable and good financial performance, indicated by optimal liquidity and solvency ratios and efficiency in asset and inventory management. PT Sido Muncul Tbk has the highest profitability ratio, while PT Kimia Farma Tbk shows poor performance with high dependence on debt and significant fluctuations in profitability. This study provides a comprehensive picture of the financial position of the pharmaceutical sector in Indonesia, which can be used as a reference for strategic decision making and company evaluation.